Exchange rate expectations of chartists and fundamentalists - Christian D. Dick; Lukas Menkhoff (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper provides novel evidence on exchange rate expectations of both chartists and fundamentalists separately. These groups indeed form expectations differently. Chartists change their expectations more often; however, all professionals expectations vary considerably as they generally follow strong exchange rate trends. In line with non-linear exchange rate-modeling, professionals expect mean reversion only if exchange rates deviate strongly from PPP. Chartists survive in currency markets since they forecast just as accurately as fundamentalists. Unexpectedly from an efficient market viewpoint, chartists even outperform fundamentalists at short horizons. Overall, these findings clearly support the chartist-fundamentalist approach.
Keywords: F31; G15; D84; 330; exchange rate formation; expectation formation; heterogeneous agent models; forecasting performance